The influence of macroeconomics and population in country of origin on tourist arrivals to Indonesia - Rachmania Nurul Fitri Amijaya; Mohammad Yusron Sholikhin; Bayu Arie Fianto (Faculty of Economics, Universitas Islam Indonesia, 2019)
This study aims giving an evaluation to develop the government and tourism agencies performance, which provides services, facilities, and infrastructures, whom Muslim-friendly, to attract the interest of Muslim tourist, that contributes to economic growth in Indonesia. It uses quantitative methods to examine the influence of macroeconomy and population in country of origin towards tourist arrivals to Indonesia. Regression panel data is used to examine the combination of time series from 2012-2017, and 5 countries from OIC, become cross-section data. It can be concluded that macroeconomy is not significant, while the population is significant towards Muslim tourist arrivals with 96% level influence. Therefore, the increasing of population from country of origin will rise tourist arrivals to Indonesia, which contributes to economic growth in Indonesia.